Environmental crime: dialectical and criminological vision - Golubev, Stanislav Igorevich; Gracheva, Julia Viktorovna; Malikov, Sergey Vladimirovich; Chuchaev, Alexander Ivanovich (Cuestiones Políticas, 2020)
Traditionally, environmental crimes have been difficult to penalize both in Russia and abroad. Russian environmental legislation is not codified, it is a complex conglomerate of a wide variety of legal acts that are condemned to take into account the classification of environmental crimes and their delimitation of related crimes. Accordingly, the article examines the status, causes and some measures to prevent environmental crimes. The general methodological basis of the research was formed by the basic provisions of the dialectical method of the study of the phenomenon of legal in its text-context relationship. All the evidence can be concluded that the reasons for the production of environmental crimes include the ineffectiveness of the activities of law enforcement agencies, economic determinants and reasons in the field of legal awareness. In addition, the analysis of the statistical table of environmental crimes recorded a clear disproportion between the real situation in the field of ecology and the fight against such crimes. At the same time, the most significant factor that distorts the real image of environmental crimes is there and recursion latency in the concrete.